Awareness of HIV testing guidelines is low among Swiss emergency doctors: a survey of five teaching hospitals in French-speaking Switzerland. - Katharine E A Darling; Nathalie de Allegri; Daniel Fishman; Reza Kehtari; Olivier T Rutschmann; Matthias Cavassini; Olivier Hugli (PLoS ONE, 2013)
BACKGROUND: In Switzerland, 30% of HIV-infected individuals are diagnosed late. To optimize HIV testing, the Swiss Federal Office of Public Health (FOPH) updated 'Provider Induced Counseling and Testing' (PICT) recommendations in 2010. These permit doctors to test patients if HIV infection is suspected, without explicit consent or pre-test counseling; patients should nonetheless be informed that testing will be performed. We examined awareness of these updated recommendations among emergency department (ED) doctors. METHODS: We conducted a questionnaire-based survey among 167 ED doctors at five teaching hospitals in French-Speaking Switzerland between 1(st) May and 31(st) July 2011. For 25 clinical scenarios, participants had to state whether HIV testing was indicated or whether patient consent or pre-test counseling was required. We asked how many HIV tests participants had requested in the previous month, and whether they were aware of the FOPH testing recommendations. RESULTS: 144/167 doctors (88%) returned the questionnaire. Median postgraduate experience was 6.5 years (interquartile range [IQR] 3; 12). Mean percentage of correct answers was 59 ± 11%, senior doctors scoring higher (P=0.001). Lowest-scoring questions pertained to acute HIV infection and scenarios where patient consent was not required. Median number of test requests was 1 (IQR 0-2, range 0-10). Only 26/144 (18%) of participants were aware of the updated FOPH recommendations. Those aware had higher scores (P=0.001) but did not perform more HIV tests. CONCLUSIONS: Swiss ED doctors are not aware of the national HIV testing recommendations and rarely perform HIV tests. Improved recommendation dissemination and adherence is required if ED doctors are to contribute to earlier HIV diagnoses.